Influence of Talent Management, Competence and Placement on Employee Performance (Human Resource Management Literature Review) - Triana Candraningrum (Dinasti International Journal of Management Science, 2023)
In the context of human resource management science, the scientific article "Article Literature Review: The Influence of Talent Management, Competence, and Placement Against Employee Performance" aims to construct a hypothesis of research influence between variables that will be used in subsequent research. This literature review was written using the library's research process, with information from internet sources like Google Scholar, Mendeley, and academic blogs. The findings of this study of the literature are as follows: 1) Talent management has an impact on employee performance; 2) competency has an impact; and 3) placement has an impact.